Realising accepted upr recommendations: challenges and realities in Malaysia’s commitment to enforce freedom of expression - Murni Wan Mohd Nor,; Syarifah Fatimah Al Zahrah Syed Hussein Al-Attas,; Lubna Sheikh Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malaysians were optimistic after the 14th General Election of 2018 (GE14) was concluded, as freedom of expression was expected to progress significantly under Pakatan Harapan (PH). It was hoped that the era of the “New Malaysia” would result in increased commitment toward realising accepted UPR recommendations. Unfortunately, Malaysia’s political climate has since experienced incidences of uncertainty and instability, which has seen three different Prime Ministers and yet another change in government administration since 2018. This has placed significant challenges on human rights reforms and impeded the process of democratisation. The objective of this study is to evaluate Malaysia’s enforcement of freedom of expression regarding the relevant UPR recommendations. It has identified certain improvements which should be supported and continued, as well as setbacks and restrictions which impede the implementation of fundamental liberties and pose added risks to the democratic rights of all Malaysians.